Improving Students’ Scientific Literacy through the Cycle-based Learning Model - Atikah Syamsi; Zulela M.S.; Yufiarti Yufiarti (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThe study is to provide an alternative science learning model of an elementary school that can invite students to improve science literacy. As observations and questionnaires of researchers in a preliminary study at two elementary schools in the city of Cirebon, West Java, it was found that based on the average results of the initial analysis of scientific literacy tests of students from the two schools, an average of 85.7% showed negative results with the ability to answer the practice of science questions in the form of literacy, which means that students have not been able to answer literacy questions test. The research method uses model development the ASSURE development model starting with Student analysis; setting goals; choose a method, media / material, use media & material; activating student involvement as well as evaluations & revisions developed by Sharon Smaldino. As for the preliminary study conducted by analyzing 5th-grade students of Madrasah Ibtidaiyah (MI) PGM and Madrasah Ibtidaiyah (MI) An-Nur Cirebon as samples and also observing teachers from the two schools, so this research produces a SIBELPOLEN model for science learning, which consists of teaching syntax, teacher roles, support system, accompaniment impact, instructional impact and designing lesson plans that can improve Science literacy competence of elementary school students.AbstrakPenelitian ini bertujuan untuk memberikan alternatif model pembelajaran Ilmu Pengetahuan Alam (IPA) di sekolah dasar dalam meningkatkan literasi sains pada siswa. Hasil observasi dan angket peneliti dalam studi pendahuluan di dua Sekolah Dasar di Kota Cirebon Jawa Barat diketahui bahwa berdasarkan rata-rata hasil analisis awal tes literasi sains siswa dari dua sekolah tersebut rata-rata 85,7% menunjukkan hasil negatif dengan kemampuan menjawab soal latihan soal IPA berupa literasi yang artinya siswa belum mampu menjawab soal tes literasi. Metode penelitian yang diterapkan pengembangan model ASSURE yang diawali dengan Student analysis; menetapkan tujuan; pilih metode, media / material, gunakan media & material; mengaktifkan keterlibatan siswa serta evaluasi & revisi yang dikembangkan oleh Sharon Smaldino. Adapun studi pendahuluan dilakukan dengan menganalisis siswa kelas V Madrasah Ibtidaiyah (MI) PGM dan Madrasah Ibtidaiyah (MI) An-Nur Cirebon sebagai sampel dan juga melakukan observasi terhadap guru dari kedua sekolah tersebut, maka penelitian ini menghasilkan model SIBELPOLEN untuk pembelajaran IPA. yang terdiri dari: sintaks pengajaran, peran guru, sistem pendukung, dampak pendampingan, dampak instruksional dan merancang rencana pembelajaran yang dapat meningkatkan kompetensi literasi sains siswa sekolah dasarHow to Cite: Syamsi, A, M. S. Zulela., Yufiart (2020). ). Improving Students’ Scientific Literacy through the Cycle-based Learning Model. TARBIYA: Journal of Education in Muslim Society, 7 (1), 133-142. doi:10.15408/tjems.v7i1.16941